POTENTIAL OF SACHA INCHI (Plukenetia volubilis L.) AS AN ANTICANCER : A SYSTEMATIC REVIEW - Fadhilah, Nadiah Farah; Nastiti, Chyntia Tresna; Zuhri, Fuad Minan (Universitas Airlangga, 2025)
Cancer is the leading cause of death worldwide. WHO estimated 20 million new cancer cases and 9.7 million deaths in 2022. The increasing incidence of cancer encourages development of new therapeutic agents for higher patient survival rate. Plant products are widely studied, one of which is Sacha Inchi (Plukenetia volubilis L.) extract. Sacha Inchi is known to have contents with anticancer potential, but information regarding its effectiveness is still limited. This systematic review aims to provide in-depth review on studies focus on anticancer potential of Sacha Inchi. The searching process was conducted in 4 databases such as National Library of Medicine (MEDLINE-PubMed), Scopus, Springerlink, and Sciencedirect. Keywords used were combination of